Rezul'taty vystuplenija rossijskich sportsmenov na II Evropejskich igrach 2019 goda v Minske - Leontyeva, L. S.; Koreneva, M. V.; Leontyeva, N. S.; Belinsky, D. V.; Shamsutdinova, L. N. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The study is devoted to the features and performance results of the national team of the Russian Federation at the II European Games of 2019, hosted by the Belarusian city of Minsk. The article discusses the special aspects of the preparation and holding, organizational and competitive indicators, competition results, etc. The performance results of the team of Russian athletes at the II European Games of 2019 have been studied and analyzed. In the research process, the following methods were used: collection, analysis and systematization of the information sources and statistical data, inductive and deductive methods. The results that were obtained during the analysis, can be widely used for historical sports disciplines, implemented in sports schools and universities. Theoretical and statistical materials were included in the lecture course of the disciplines "Olympic education" and "History of physical education".